Preliminary results of positive ion mass spectrometry based on a 2.45 GHz ECR ion source and a non-metallic gas target. Issue 1 (1st April 2022) - Li, K.; Peng, S.X.; Ma, T. H.; Wu, W.B.; Jiang, Y. X.; Cui, B.J.; Zhang, A. L.; Sun, J.; Guo, Z. Y.; Chen, J. E.
Abstract: Positive-ion mass spectrometry (PIMS) is a positive-to-negative ion conversion metrology that just operated on the opposite of traditional accelerator mass spectrometry (AMS) on high-precision radiocarbon dating. With a higher efficient simple structure plasma ion sources instead of AMS sputter ion sources, lower ion energy (tens keV) in place of MeV, and limited footprint facility, PIMS will be a powerful competitor to AMS in the future. To precisely measure 14 C, interference of molecular isobars (such as 12 CH2, 13 CH) will be eliminated with higher charged ions (charge state ≥ 3; molecular cations 12 CH2 2+ is metastable, can be eliminated by higher stripping pressure.), nitrogen will be eliminated inside the charge-exchange cell (CXC) through charge exchanging with target gas. To demonstrate the probability of PIMS with a 2.45 GHz ECR ion source, an experiment was launched at Peking University (PKU). A compact permanent magnet 2.45 GHz ECR ion source is designed to produce carbon ions from CO2 . A CXC unit was installed after the extraction system and ethylene is chosen as charge exchange gas. Preliminary experiments prove that more than hundreds of microamp of C 2+ beam can be produced with this ECR source. By injecting ethylene into CXC, several microamp C - beam was detected and the C 2+ ions charge exchange efficiency to C - ions can reach close to 5%.